HOW TO SOLVE POLYNOMIAL EQUATION OF DEGREE 5

To solve a polynomial equation of degree 5, we have to factor the given polynomial as much as possible. After having factored, we can equate factors to zero and solve for the variable.  

Example 1 :

Solve :

6x5 - x4 - 43x3 + 43x2 + x - 6 = 0

Solution :

By trial and error, we can check the values 1 or -1 or 2 or -2...... as a zero for the above equation using synthetic division. 

When we check with the value 1, we get remainder zero. So, x = 1 is one of the zeros. 

Resulting equation :

6x4 + 5x3 - 38x2 + 5x + 6 = 0

Dividing both sides by x2.

6x4/x+ 5x3/x2 - 38x2/x2 + 5x/x2 + 6/x2 = 0

6x2 + 5x - 38 + 5/x + 6/x2 = 0

6(x2 + 1/x2) + 5 (x + 1/x) - 38 = 0 ----(1)

Let y = x + 1/x.

y2 = (x + 1/x)2

y= x2 + 2(x)(1/x) + (1/x)2

y= x2 + 2 + 1/x2

y- 2 = x2 + 1/x2

(1)----> 6(y2 - 2) + 5y - 38 = 0

6y2 - 12 + 5y - 38 = 0

6y2 + 5y - 50 = 0

6y2 - 15y + 20 y - 50 = 0

3y(2y - 5) + 10(2y - 5) = 0

(3y + 10)(2y - 5) = 0

3y + 10 = 0

y = -10/3

2y - 5 = 0

y = 5/2

When y  =  -10/3,

(x2 + 1)/x = -10/3

3(x2 + 1) = -10x

3x2 + 3 = -10x

3x2 + 10x + 3 = 0

(3x + 1)(x + 3) = 0

x = -1/3 and 3

When y = 5/2,

x + 1/x = y

(x2 + 1)/x = 5/2

2(x2 + 1) = 5 x

2x2 + 2 - 5x = 0

2x2 - 5x + 2 = 0

(2x - 1)(x - 2) = 0

x = 1/2 and 2

Therefore the five zeros are 1, -1/3, 3, 1/2 and 2.

Example 2 :

Solve :

8x5 - 22x4 - 55x3 + 55x2 + 22x - 8 = 0

Solution :

When we check with the value 1, we get remainder zero. So, x = 1 is one of the zeros. 

Resulting equation :

8x4 - 14x3 - 69x2 - 14x + 8 = 0

Dividing both sides by x2.

8x4/x- 14x3/x2 - 69x2/x2 - 14x/x2 + 8/x2 = 0

8x- 14x - 69 - 14/x + 8/x2 = 0

8(x2 + 1/x2) - 14(x + 1/x) - 69 = 0 ----(1)

Let y = x + 1/x. 

y2 = (x + 1/x)2

y= x2 + 2(x)(1/x) + (1/x)2

y= x2 + 2 + 1/x2

y- 2 = x2 + 1/x2

(1)----> 8(y2 - 2) - 14y - 69 = 0

8y2 - 16 - 14y - 69 = 0

8y2 - 14y - 85 = 0

(2y + 5)(4y - 17) = 0

2y + 5 = 0

y = -5/2

4y - 17 = 0

y = 17/4

When y = -5/2,

x + 1/x = y

(x2 + 1)/x = -5/2

2(x2 + 1) = -5x

2x2 + 2 + 5x = 0

2x2 + 5x + 2 = 0

2x2 + 4x + 1x + 2 = 0

2x(x + 2) + 1(x + 2) = 0

(2x + 1)(x + 2) = 0

x = -1/2 and -2

When y = 17/4,

x + 1/x = y

(x2 + 1)/x = 17/4

4(x2 + 1) = 17x

4x2 + 4 = 17x

4x2 - 17x + 4 = 0

(4x - 1)(x - 4) = 0

x = 1/4 and 4

Therefore the five zeros are  1, -1/2, -2, 1/4 and 4.

Example 3 :

Solve :

6x5 + 11x4 - 33x3 - 33x2 + 11x + 6 = 0

Solution :

When we check with the value -1, we get remainder zero. So, x = -1 is one of the zeros. 

Resulting equation :

6x4 + 5x3 - 38x2 + 5x + 6 = 0

Dividing both sides by x2.

6x4/x+ 5x3/x2 - 38x2/x2 + 5x/x2 + 6/x2 = 0

6x+ 5x - 38 + 5/x + 6/x2 = 0

6(x2 + 1/x2) + 5(x + 1/x) - 38 = 0 ----(1)

Let y = x + 1/x. 

y2 = (x + 1/x)2

y= x2 + 2(x)(1/x) + (1/x)2

y= x2 + 2 + 1/x2

y- 2 = x2 + 1/x2

(1)----> 6(y2 - 2) + 5y - 38 = 0

6y2 - 12 + 5y - 38 = 0

6y2 + 5y - 50 = 0

6y2 - 15y + 20y - 50 = 0

3y(2y - 5) + 10(2y - 5) = 0

(3y + 10)(2y - 5) = 0

3y + 10 = 0

y = -10/3

2y - 5 = 0

y = 5/2

When y = -10/3, 

x + 1/x = y

(x2 + 1)/x = -10/3

3(x2 + 1) = -10x

3x2 + 3 = -10x

3x2 + 10x + 3 = 0

3x2 + 9x + x + 3 = 0

3x(x + 3) + 1(x + 3) = 0

(x + 3)(3x + 1) = 0

x = -3 and -1/3

When y = 5/2, 

x + 1/x = y

(x2 + 1)/x = 5/2

2(x2 + 1) = 5x

2x2 + 2 - 5x = 0

2x2 - 5x + 2 = 0

2x2 - 4x - x + 2 = 0

2x(x - 2) - 1(x - 2) = 0

(2x - 1)(x - 2) = 0

x = 1/2 and 2

Therefore the five zeros are -1, -3, -1/3, 1/2 and 2.

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Unit Rates

    Dec 02, 22 04:18 PM

    Unit Rates - Concept - Examples with step by step explanation

    Read More

  2. Adding and Subtracting Fractions Worksheet

    Dec 02, 22 07:27 AM

    Adding and Subtracting Fractions Worksheet

    Read More

  3. Relation between Radian and Degree

    Dec 02, 22 07:16 AM

    Relation between Radian and Degree

    Read More